PENCIPTAAN BUKU REFERENSI MASAKAN SEMANGGI SEBAGAI UPAYA PELESTARIAN KULINER TRADISIONAL SURABAYA - Akbar, Abdul Aziz (Jurnal Art Nouveau, 2014)
Abstract: Surabaya has several one of which is a traditional food of semanggi Surabaya. However, over the times and technology make foreign food products such as ready meals (fast food) and foreign restaurant businesses thrive in big cities. Society makes a fast food restaurant and the foreign key option than traditional foods. The purpose of creation to create a book that discusses the focus of semanggi Surabaya can provide knowledge to the target audience of Semanggi Surabaya. The design is done by using qualitative methods, namely observation, interviews and literature studies to conclude the concept in the design process. Through the process of data analysis, found the keyword